AN ANALYSIS OF COMMUNICATIVE FUNCTIONS IN CONVERSATIONS IN AN ENGLISH TEXTBOOK - Nisrina Nisrina; Isti Komah; Rahma Sarita; Oriza Sativa; Rahmad Ade Akbar (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2026)
This study aims to analyze the variations of communicative functions in the conversations of an English textbook for Grade VIII Junior High School based on Michael Halliday’s theory of communicative functions. Communicative competence is the primary goal in English language learning; thus, conversational materials in textbooks must reflect real-life communication situations. This study employed a descriptive qualitative method. The research data consisted of dialogue transcripts found in the textbook, which were then classified into seven types of communication functions according to Halliday, namely instrumental conversation, social conversation, dialogue, expressive conversation, ritual conversation, discussion, and debate. The results indicate that only four types of communicative functions dominantly appear in the textbook, which include instrumental conversation (to obtain information/assistance), social conversation (to build interpersonal relationships), dialogue (two-way information exchange), and expressive conversation (expressions of emotion/admiration). Meanwhile, the other three functions ritual conversation, discussion, and debate were not found in the analyzed data. This shows that although the textbook has successfully supported basic everyday communication competence, the presented materials remain limited and under-facilitate students' higher-order thinking skills (HOTS), such as argumentation and problem-solving skills. Therefore, it is recommended that curriculum developers and future textbook writers integrate a more balanced variety of communication functions to comprehensively support students' cognitive and intercultural development.